PENGARUH PEMBERIAN UMPAN BALIK BERDASARKAN HASIL PENILAIAN UNJUK KERJA TERHADAP MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PRAKTEK INSTRUMEN KEYBOARD DI KELAS X-2 SMK NEGERI 7 PADANG - Dilla Triyanda Novera; Yos Sudarman (SENDRATASIK UNP, 2018)
Abstract This article aims to explain that giving feedback based on assessment results associated with motivation influence student learning, including explain also that giving feedback based on the results of the assessment in question can also be differentiating learning motivation of students in learning the practice keyboard instruments in class X-2 music SMK Negeri Padang 7. This type of research is the study of the quantitative approach to experimentation. Population studies on all the X-class students music SMK Negeri Padang 7 who study the practice keyboard instruments in odd semester 2017/2108. The research sample is X-grade music class 2 and X-3, which provided the music class experiment research and control. The main research instrument is the data the results of the assessment and the question form, while an extra instrument observation notes is learning. Results of the study proved that the two hypotheses of the research presented in this study are both accepted, either unilaterally by the tested relationship test correlation techniques influence maupu test two parties by comparing earnings results now between the experimental and control. Test results correlation one party proves that the value of the relationship between the influence the giving feedback based on the results of the assessment in the classroom experiment = 0.76 and in control class = 0.54. While the difference now between classes results difference experiments and classroom control is at 95, in which the score now experimental class higher than the class of the control. Key words:   influence, feedback, Performance, Learning Motivation of students, Keyboard Instruments